Classroomscreen's Timer and Work Symbols Widgets: Encouraging Students' Communication During Group Works in English Classes - Esparrago-Kalidas, Adeva Jane; Manla, Edralin; Dampor , Ninna Norika R.; Labnotin , Roy Vincent J.; Quintana, Angelica Chriselle; Taloon, Twinkle L. (Universitas Lancang Kuning, 2024)
This action research uses Classroomscreen, an interactive tool that has a variety of features and options for facilitating learning like widgets such as timer and work symbols, to encourage communication during group works. The research used a practical action research design that utilized mixed methods to address the study's problem and was conducted at a private Junior High School in the Philippines. The researchers introduced the said application and conducted an observation before and during its use. After the proposed intervention, the researchers conducted a focus group discussion and computed the data using Wilcoxon Signed Rank Test. The results showed that students can better concentrate and pay attention, ask and answer questions, and communicate better over-all during groupworks when they were using Classroomscreen. Thus, the researchers recommend that teachers maximize the use of Classroomscreen in both face to face and online learning.